Efeito da inundação na sobrevivência de Conyza spp. em terras baixas e seu manejo em arroz irrigado - Puntel, Simone (2024)
The introduction of soybean in rotation with rice has favored the presence of Conyza spp. in lowland areas. This study aimed to determine the effect of flooding on the survival of Conyza spp. and to identify potential genes related to flood tolerance (chapter 1), estimate its competitiveness (chapter 2), and evaluate its chemical management in irrigated rice (chapter 3). The experiments in chapter 1 were conducted in a greenhouse using a completely randomized design (CRD), with three replications. When the Conyza spp. biotypes reached 15 cm in height, they were subjected to a 4 cm water layer for 15 days. Different Conyza spp. biotypes collected from the state of Rio Grande do Sul were tested. The variables evaluated included visual injury, height, root dry mass, and shoot dry mass at the end of the experiments. For gene evaluation, treatments were arranged in a factorial design, where factor A corresponded to biotypes (TPA, CSL, and ITQ) and factor B to the sampled tissue (new and old leaves) at 0, 4, and 10 days after flooding. The relative expression of the genes ALT2, PDC1, GLB1, SUB1A, and ERF2 was measured. The two experiments in chapter 2 were conducted in a greenhouse, also using a CRD, with four replications under two irrigation scenarios: flooded and sprinkler irrigation. Treatments were arranged in a factorial design, where factor A was the timing of Conyza spp. establishment relative to the rice crop (before or simultaneously) and factor B was the population density (0, 1, 2, 4, and 8 plants per pot) competing with one rice plant. Variables evaluated for rice included height, number of leaves and tillers, root dry mass, and shoot dry mass. For chapter 3, two greenhouse experiments and one field experiment were conducted using a randomized block design (RBD), with four replications. In the greenhouse, treatments were arranged in a factorial design, where factor A was the presence or absence of a water layer after herbicide application, and factor B comprised different herbicides. For the field experiment, treatments consisted of the various herbicides used. The results indicate that the Conyza spp. biotypes SAN, TPA, SAU, FDS, and SMA4 do not tolerate flooding, whereas BRO, CSL, ITQ, JCS, RES1, SMA1 and SMA2 exhibited tolerance to the tested flooding condition. The genes ALT2, PDC1, ERF2, GLB1, and SUB1A are potential candidates for further study. The presence of Conyza spp. established before the emergence of rice negatively impacts the crop. The herbicides florpyrauxifen-benzyl, quinclorac, triclopyr-butyl, and saflufenacil demonstrated over 80% control of Conyza spp. In conclusion, certain Conyza spp. biotypes have adapted to flooding, potentially associated with the expression of plant energy metabolism genes (ALT2, PDC1, GLB1) and ethylene-related genes (ERF2 and SUB1A). Conyza spp. is more competitive than rice when established prior to crop emergence. Chemical management of Conyza spp. is effective through post-emergence herbicide applications in rice.